The effects of party identification on perceptions of pledge fulfilment: evidence from Portugal - Belchior, A. M. (2019)
Empirical research has found that, despite citizens’ perceptions to the contrary, political parties tend to deliver on their campaign promises. What are the reasons for this mismatch between perceptions and performance? Research to date has paid insufficient attention to the reasons for such a mismatch, neglecting the effects of political predispositions such as party identification and sympathy for the government. This article argues that it is such political predispositions that cause biased perceptions of pledge fulfilment. Bias towards perceiving pledges as unfulfilled is expected to be higher for voters whose political predispositions are more unfavourable to government. The argument is supported by data on Portuguese voters and party manifestos in the 2011 election, contributing to better understanding of the mechanisms of political accountability.